Addressing the Effect of Mindfulness Based Stress Reduction and Mindfulness Based Approaches in Sport Injury: A Systematic Review - Warhel Mohammed (College of Physical Education and Sport Sciences, 2021)
The aim of this review was to determine the effect of mindfulness on the psychological demands of injured athletes following formal and informal mindfulness practice across seven major studies that were graded and summarized. As a result, this review will provide a comprehensive examination of MBSR's theoretical and practical application in the sport rehabilitation process. The scientific search was conducted via the Web of Science, PubMed, Scopus, and CINAHL, to find research that had been published between (2011-2020). Using a combination of these groups of keywords, a manual search has also been supplemented. The first and second researcher extracted relevant data from the studies. As for the information on study design, study population, stress reduction measurement, duration of intervention, and results were extracted in a standardized form. The initial search yielded 240 articles. A total of nine studies were deemed applicable following application of the inclusion and exclusion criteria. Most studies in this review used quantitative methods and two studies used mixed approaches. One study used both quantitative and qualitative methods, whilst another study used both experimental and quantitative methods. They assessed both pain tolerance and the perception of pain in injured athletes during a Cold Pressor Test. The rest of the studies were descriptive and most of the studies applied MBSR techniques or other mindfulness-based approaches with injured athletes. One study used a cross-sectional study design. There was a mix of methodology designs that had been used by the researchers. This systematic review clarified a promising outcome to adapt MBSR into sport injury rehabilitation. This is through formal and informal mindfulness practice by practitioners. MBSR is not only used with clinical populations, but also with non-clinical populations. Thus, the integration of MBSR and MBA into sport therapy would create a valuable understanding regarding mindfulness practice in sport, in both theoretical and practical knowledge.